Perils of excessive credit growth: evidence from 11 new EU member states - Laivi Laidroo; Kadri Männasoo (Baltic Journal of Economics, 2014)
We investigate the association between banks' credit expansion and loan loss reserves on a panel of banks from 11 new EU member countries from Central and Eastern Europe during 2004–2010. Unused committed credit lines capture the decline in banks' risk aversion being associated with a supply shift. As the existence of loan commitments may lead to overlending, we expect that banks with a higher share of unused committed credit lines are more prone to subsequent increase in loan loss reserves. The system and difference GMM estimations as well as pooled OLS and panel fixed effects estimations confirm that an excessive credit supply, reflected in overextension of committed credit lines, predicts increase in bank loan loss reserves two years ahead while controlling for bank asset returns, real growth in loan portfolio, country GDP, inflation and EBRD banking sector reform index. This stresses the importance of credit lines monitoring by regulatory and supervisory authorities for timely recognition of credit overextension episodes. The negative association between loan loss reserves and real GDP growth was affirmed.
Keywords: G21; 330; banks; Central and Eastern Europe; committed credit lines; credit growth; credit quality